Gender pay gap reporting: important, undesirable or irrelevant? - Brown, Duncan (Brighton, 2016)
"The UK’s median all-employee gender earnings gap is 19.1 per cent, compared to the EU average of 16.4 per cent. That’s equivalent to a loss of